Association between atrial fibrillation, anticoagulation, risk of cerebrovascular events and multimorbidity in general practice: a registry-based study. Issue 1 (December 2016) - Vanbeselaere, Vigdis; Truyers, Carla; Elli, Steven; Buntinx, Frank; De Witte, Harrie; Degryse, Jan; Henrard, Séverine; Vaes, Bert
Abstract Background To date, there has been no comprehensive study on the association between atrial fibrillation (AF) and multimorbidity. The present study investigated the epidemiology of AF and the association between multimorbidity and the onset of AF. In addition, the correlation between multimorbidity and the use of anticoagulants and the risk of cerebrovascular events considering multimorbidity was explored in AF patients. Methods Intego is a primary care registry network in Belgium. A case–control study was performed using Intego data from a 10-year time interval (2002 to 2011). All patients aged 60 years and older in 2002 who had developed new AF between 2002 and 2011 were selected, as well as a group of matched control patients. In addition, the prescription of anticoagulants and incident cerebrovascular events were recorded in patients with AF. Results AF showed a prevalence of 5.3 % in 2002, and an upward trend was observed between 2002 and 2011. In all, 1830 patients with AF and 6622 control patients were included. AF patients had significantly more comorbidities (mCCI (modified Charlson Comorbidity Index) 5 ± 2 vs 4 ± 2, P <  0.001). In addition, 9.7 % of patients with AF developed a cerebrovascular event (mean follow-up time of 2.7 ± 2.5 years). Both the under- and overuse of anticoagulants was observed. Of the 49 % of patients with AF who were considered at high risk (CHADS2  ≥ 2), 50 % received anticoagulants in the first six months after diagnosis, whereas 49 % of patients who were at low risk (CHADS2  = 0) did not. Conclusions AF is highly prevalent in older primary care patients and is significantly associated with multimorbidity. A discrepancy between the guidelines and clinical practice of anticoagulant use was observed. As multimorbidity seems to play a role in this, further qualitative research to study the perception and motives of the general practitioner is needed.